22 The legacy effect of coronary perforation complicating PCI-CTO: an analysis of 26, 807 cases from the BCIS database. (27th November 2017) - Kinnaird, Tim; Anderson, Richard; Ossei-Gerning, Nicholas; Cockburn, James; Sirker, Alex; Ludman, Peter; Belder, Mark de; Walsh, Simon; Hanratty, Colm; Smith, Elliot; Strange, Julian; Spratt, James; et al.
Abstract : Background: Coronary perforation (CP) during chronic total occlusion percutaneous coronary intervention for stable angina (CTO-PCI) is a rare but serious event. The evidence base is limited and the long-term effects unclear. Methods: Data analysed from the British Cardiovascular Intervention Society dataset on all CTO-PCI procedures performed in England and Wales between 2006 and 2013. Multivariate logistic regressions and propensity scores were used to identify predictors of CP and its association with outcomes. Results: A total of 376 CP were recorded from 26, 807 CTO-PCI interventions (incidence of 1.4%) with an increase in frequency during the study period (p=0.012). Patient-related factors associated with an increased risk of CP were age and female gender. Procedural factors indicative of complex CTO intervention strongly related to an increased risk of CP with a close relationship between the number of complex strategies utilised and CP evident (p=0.008 for trend). Tamponade occurred in 16.6% and emergency surgery in 3.4% of cases. Adverse outcomes were frequent in those patients with perforation including bleeding, transfusion, MI and death. A legacy effect of perforation on mortality was evident, with an odds ratio for 12 month mortality of 1.60 for perforation survivors compared to matched non-perforation survivors without a CP (p<0.0001). Conclusions: Many of the factors associated with an increased risk of CP were related to CTO complexity. Perforation was associated with adverse outcomes, with a legacy effect on later mortality after CP also observed.